Cinematic Rendering With Positive Oral Contrast: Virtual Fluoroscopy. Issue 5 (September 2019) - Rowe, Steven P.; Chu, Linda C.; Fishman, Elliot K.
Abstract : Abstract: Recently, a novel 3-dimensional visualization methodology for volumetric computed tomography data has become available. This method, known as cinematic rendering, uses an advanced lighting model to create photorealistic images from standard computed tomography acquisition data composed of isotropic voxels. We have observed that cinematic rendering visualizations in which patients have been administered dense, positive oral contrast do not have any substantive visual artifacts and can be used to demonstrate bowel pathology to advantage (ie, "virtual fluoroscopy"). In this technical note, we describe our acquisition and visualization parameters, and we also include demonstrative examples.